2022
DOI: 10.3390/cancers14246206
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus Group B3 Has Oncolytic Activity against Colon Cancer through Gasdermin E-Mediated Pyroptosis

Abstract: Colon cancer is the second leading cause of cancer-related death, and there are few effective therapies for colon cancer. This study explored the use of coxsackievirus group B3 (CVB3) as an oncolytic virus for the treatment of colon cancer. In this study, we verified that CVB3 induces death of colon cancer cell lines by directly observing cell morphology and Western blot results, and observed the oncolytic effects of CVB3 by constructing an immunodeficient nude mice model. Our data show that CVB3 induces pyrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Within the CD8 high population, PDGFRb high status delineates patients with impaired survival. Previous reports describe elevated evasion of immune surveillance mediated by intratumoral transforming growth factor-beta (TGF-β) signaling, which is positively associated to PDGFRb expression ( Baba et al, 2022 ; Zhang Y. et al, 2022 ). In an analysis of metastatic urothelial cancer, a high TGF- β signature in fibroblasts attenuated response to PD-L1 blockade and contributed to CD8 T-cell exclusion ( Mariathasan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the CD8 high population, PDGFRb high status delineates patients with impaired survival. Previous reports describe elevated evasion of immune surveillance mediated by intratumoral transforming growth factor-beta (TGF-β) signaling, which is positively associated to PDGFRb expression ( Baba et al, 2022 ; Zhang Y. et al, 2022 ). In an analysis of metastatic urothelial cancer, a high TGF- β signature in fibroblasts attenuated response to PD-L1 blockade and contributed to CD8 T-cell exclusion ( Mariathasan et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… 149 The oAds-armed apoptotic protein, encoded by the VP3 gene of chicken anemia virus (CAV), induces pyroptosis by cleaving caspase-3 and GSDME, and significantly inhibits the growth of colorectal tumors. 150 Other OVs, such as coxsackievirus B3, 151 HSV-1, 152 NDV, 153 etc., have also adopted the death mode, and these pyroptosis-based anticancer drugs may open up new possibilities for OV therapy in the future.…”
Section: The Arsenal For Ovs: Modification Strategiesmentioning
confidence: 99%
“…Studies have demonstrated that GSDME-mediated pyroptosis is also essential to the development of colorectal cancer [ 119 ]. Coxsackievirus group B3 (CVB3) is able to induce pyroptosis in colon cancer cell lines both in vivo and in vitro [ 120 ]. Mechanistically, CVB3-induced pyroptosis is promoted by ROS, which activates the caspase-3/GSDME pathway to produce pores in the plasma membrane [ 120 ].…”
Section: Role Of Gsdme-mediated Pyroptosis In Cancer Therapymentioning
confidence: 99%
“…Coxsackievirus group B3 (CVB3) is able to induce pyroptosis in colon cancer cell lines both in vivo and in vitro [ 120 ]. Mechanistically, CVB3-induced pyroptosis is promoted by ROS, which activates the caspase-3/GSDME pathway to produce pores in the plasma membrane [ 120 ]. These findings suggest that CVB3 is effective in treating colon cancer through the GSDME-mediated pyroptosis pathway.…”
Section: Role Of Gsdme-mediated Pyroptosis In Cancer Therapymentioning
confidence: 99%